ANALISIS WACANA SARA MILLS PEMBERITAAN BLAMING VICTIM PEREMPUAN KORBAN PERKOSAAN PADA OKEZONE.COM - Akbar, Dzulhi Dwiki; Abidin, Sholihul (SCIENTIA JOURNAL, 2020)
This research focuses on how to describe position of women who are victims of rape in an online newspaper okezone.com. This research was chosen because of the many news agendas in the form of texts and pictures that tend to blame women in a rape. Through this research, there are four news items that contain elements of blaming rape victims in their news writing. Okezone.com was chosen as a news source because it is the first-ranked owner to be visited and accessed in 2019 according to the Alexa.com website. Which has a very high level of consumption compared to other online news portals.In researching the news, researchers used a critical discourse analysis of the Sara Mills model that concentrated on the position of women in reporting. In the results of the study, it was found from the four news items that were chosen that contained women as the party who contributed to the rape. This can be seen from the selection of syllables chosen by news writers.